Past, present, and future of earnings management research - Thu Hien Bui (Cogent Business & Management, 2024)
Earnings management has been a subject of extensive research, experiencing substantial growth recently and anticipated to continue in the years ahead. This paper employs bibliometric analysis, examining the Scopus database of publications from 1993 to 2021, to enhance our understanding of earnings management. There is a remarkable growth in earnings management research, with 54% of publications emerging from 2016 to 2021, peaking at 226 papers in 2021. Kim Y. and Alahada M. are leading contributors with ten publications each, while Kim J.-B. stands out with an impressive 1,056 citations across eight documents. Active contributors to earnings research are from the US, China, the UK, and Australia. In addition, this paper discusses four distinct themes within earnings management, including the motives and characteristics of earnings management activities, real and accrual-based earnings management, the relationship between corporate governance and earnings management, and earnings management and market performance. More importantly, it highlights future research opportunities, emphasizing the need to explore real earnings management as an alternative measurement and addressing topics like gender diversity, family firms, and leverage in understanding the magnitude of earnings management. Notably, the study's findings provide insights to develop the research on earnings management, especially in the emerging market finance context.
Keywords: 650; Earnings management; real earnings management; bibliometric analysis; emerging market; VOSviewer